Parental Stress Experience and Age of Mothers and Fathers After Preterm Birth and Admission of Their Neonate to Neonatal Intensive Care Unit; A Prospective Observational Pilot Study - Pichler-Stachl, Elisabeth; Urlesberger, Pia; Mattersberger, Christian; Baik-Schneditz, Nariae; Schwaberger, Berndt; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2019)
Background: Preterm birth is associated with increased stress of parents that might influence the parental-child interaction, thus potentially having influence on the neurobehavioral development of the preterm infants. However, little is known concerning the age dependency of parental stress after preterm birth. Objective: The aim of the present study was to examine the age dependency of stress in mothers and fathers after preterm birth and neonatal intensive care unit (NICU) admission of their infant. Methods: In a prospective observational pilot study 47 mothers and 47 fathers completed the parental stress scale; NICU (PSS:NICU) questionnaire within 72 hours after delivery. This questionnaire measures parental stress after preterm birth with three subscales “Looks and Behave” of the child, “Parental Role Alteration” and “Sights and Sounds”. Stress levels of mothers and fathers were compared and correlated to the age of mothers and fathers, respectively. Results: Parental stress experience after preterm birth tended to be higher in mothers compared to fathers. Mothers showed a significant positive correlation of the “Sights and Sounds” Scale and age, whereas fathers did not show any significant age dependency of stress. Conclusion: In mothers stress level increases with increasing age after preterm birth and admission of their infant to NICU, whereas fathers did not show any significant age dependency of stress.